(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2021)
This work is the result of the first systematization on the impact of situated learning, from the launch of the Extension Program "Integrating knowledge to strengthen internal and external communication in Health Institutions" that has been running since 2017. Since that date, students from three cohorts of the Bachelor of Social Communication, have experienced and experienced from the critical extension rooted in the territory, part of their professional training oriented towards communication and health. Thus, the curricularized socio-educational practices and enabled through the proposal of the social classroom, from the educating group and the participatory methodology, constitute the desirable scenario for the planning and management of a communicational perspective that puts the linking practices at the center. This visibility, added to the dialogue of acquired knowledge and learned skills, responded to specific demands of the institutional actors in each interaction. With a diverse journey and accumulated experiences that would exceed the length of this writing, a selection of cases was made for this notebook that will continue to be deepened in future deliveries.